Peningkatan Kompetensi Teknologi Informasi dan Komunikasi Bagi Guru Paud Dengan Pelatihan Microsoft Powerpoint dan Access - Safitri Juanita; Ita Novita; Muhammad Anif (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
The role of Information and Communication Technology (ICT) in the learning process in kindergarten is significant, especially in assisting teachers in evaluating learning and making interactive and communicative learning media. However, the PERAK Foundation, which has 9 PAUD in Petukangan Utara, South Jakarta, does not yet have a computer laboratory facility or provide computer facilities in each class or provide computers to PAUD teachers to assist teachers in the teaching and learning process. In addition, most of the PAUD teachers at Yayasan Perak are over 40 years old and technologically savvy. So that some of the things above hinder the application of ICT to PAUD teachers at the PERAK Foundation. Facing this problem, FTI proposed computer application training activities for PAUD teachers at the PERAK Foundation. The computer application training program aims to improve ICT skills or competencies for PAUD teachers, especially in using learning media. Based on the evaluation results of training activities carried out by the FTI Lecturer Team at Budi Luhur University in collaboration with the PERAK Foundation. It can be concluded that Microsoft PowerPoint and Access training activities have positively impacted efforts to improve information and communication technology competencies, especially for PAUD teachers at the PERAK Foundation